Perceived behavioral control regarding regular physical activity and healthy diet: An observational study among school-going adolescents in an urban area of West Bengal, India - Sweety Suman Jha; Madhumita Dobe; Chandrashekhar Taklikar; Arista Lahiri (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Healthy children are the foundation for a healthy and developing nation. Perceived behavioral control (PBC), comprising control belief and perceived power, is a person's perception of the ease or difficulty of performing the behavior of interest. For facilitating regular physical activity and regular healthy dietary practices among the adolescents, PBC is an important construct to develop and implement appropriate interventions. The aim is to assess PBC to perform regular physical activity and regular healthy dietary practices and measure their statistical relationship among the school-going adolescents in an urban area in West Bengal. MATERIALS AND METHODS: A school-based cross-sectional study was conducted among 251 adolescents aged 12-16 years after taking consent and assent for participation in the study. Data were collected with self-administered questionnaire on sociodemographic variables and the two domains of PBC, i.e., control beliefs and perceived power, related to regular physical activity and regular healthy dietary practices. Each PBC total score was calculated by multiplying control belief score and perceived power score for each respondent. Partial correlation coefficient was calculated between regular healthy dietary practices and regular physical activity. RESULTS: Among the total 251 responses analyzed, 34.7% and 27.5% students belonged to age group 14 and 15, respectively. It was observed that the mean (± standard deviation) score of PBC regarding regular healthy dietary practices was 100.7 (±27.7) and for regular physical activity was 106.0 (±21.4). The correlation between PBC of regular healthy dietary practices and regular physical activity was 0.421 and was statistically significant. CONCLUSION: In case PBC score over any behavior is higher, behavioral intention and ultimately chances of performing that particular behavior increases. Designing appropriate school-based health promotion strategies can lead to healthier children fostering regular healthy dietary practices and regular physical activity in their homes and communities.